Convergence Theorems for Non-Self Mappings in CAT(0) Spaces. (3rd June 2017) - Tufa, Abebe R.; Zegeye, H.; Thuto, M.
ABSTRACT: In this paper, we prove strong convergence of Mann iterative schemes to fixed points of multi-valued demicontractive non-self mappings in complete CAT(0) spaces under appropriate conditions. In addition, △− convergence or strong convergence of Mann iterative scheme to a fixed point of single-valued k -strictly pseudocontractive non-self mapping is obtained. Our theorems improve and unify most of the results in the literature.